Transmission of 200 G PDM-CSRZ-QPSK and PDM-16 QAM With a SE of 4 b/s/Hz - Jianjun Yu; Ze Dong; Hung-Chang Chien; Zhensheng Jia; Xinying Li; Di Huo; Gunkel, M.; Wagner, P.; Mayer, H.; Schippel, A. (Journal of lightwave technology, 2013)
We have realized the first field transmission of 8 × 216.8-Gb/s Nyquist wavelength-division-multiplexing (N-WDM) signals over 1750-km G.652 fiber consisting of 950-km real and 800-km lab fibers with erbium-doped fiber amplifier (EDFA)-only amplification. The average loss per span is 21.6 dB. Each channel is modulated with 54.2-Gbaud (216.8-Gb/s) polarization-division-multiplexing carrier-suppressed return-to-zero quadrature-phase-shift-keying (PDM-CSRZ-QPSK) data on a 50-GHz grid giving a record spectral efficiency (SE) of 4 b/s/Hz. Digital post filtering and 1-bit maximum likelihood sequence estimation (MLSE) are introduced into the offline digital signal processing (DSP) at the receiver to suppress noise, linear crosstalk and filtering effects. We have also investigated the co-transmission of 200 G PDM-CSRZ-QPSK and 200 G PDM 16-ary quadrature-amplitude-modulation (PDM-16 QAM) signals on a 50-GHz grid, and found that PDM-CSRZ-QPSK signals have better bit-error-rate (BER) performance for both back-to-back and 700-km transmission cases. Meanwhile, PDM-16 QAM signals are subject to larger crosstalk from the neighboring Nyquist QPSK channels.